Proteasome inhibitors induced caspase-dependent apoptosis and accumulation of p21WAF1/Cip1 in human immature leukemic cells - Naujokat, Cord; Sezer, O.; Zinke, H.; Leclere, A.; Hauptmann, S.; Possinger, K. (European journal of haematology, 2000)
The 26S proteasome is a non-lysosomal multicatalytic protease complex for degrading intracellular proteins by ATP/ubiquitin-dependent proteolysis. Tightly ordered proteasomal degradation of proteins critical for cell cycle control implies a role of the proteasome in maintaining cell proliferation and cell survival. In this study, we demonstrate that cell-permeable proteasome inhibitors, lactacystin, benzyloxycarbonyl(Z)-leucyl-leucyl-leucinal (ZLLLal; MG-132) and 4-hydroxy-5-iodo-3-nitrophenylacetyl-leucyl-leucyl-leucine vinyl sulfone (NLVS), induce apoptosis abundantly in p53-defective leukemic cell lines CCRF-CEM, U937 and K562 as well as in myelogenic and lymphatic leukemic cells obtained from adult individuals with relapsed acute leukemias. Leukemic cell apoptosis induced by the proteasome inhibitors was dependent on activation of caspase-3 and related caspase family proteases, because caspase-3 inhibitor N-acetyl-L-aspartyl-L-glutamyl-L-valyl-L-aspartal (Ac-DEVD-cho) and, more effectively, the general caspase-inhibitor N-benzyloxycarbonyl-L-valyl-L-alanyl-L-aspartate fluoromethylketone (Z-VAD-fmk) were capable of blocking apoptosis induced by lactacystin, ZLLLal or NLVS. Induction of apoptosis by lactacystin or ZLLLal was accompanied by cell cycle arrest at G2/M phase and by accumulation and stabilization of cyclin-dependent kinase inhibitor p21WAF1/Cip and tumor suppressor protein p53. A role of p53 in mediating apoptosis or induction of p21WAF1/Cip1 was ruled out since CCRF-CEM and U937 cells express non-functional mutant p53, and K562 cells lack expression of p53. Viability and hematopoietic outgrowth of human CD34+ progenitor cells treated with lactacystin were slightly reduced, whereas treatment of CD34 + cells with ZLLLal or the cytostatic drugs doxorubicin and gemcitabine resulted in markedly reduced viability and hematopoietic outgrowth. These results demonstrate a basic role of the proteasome in maintaining survival of human leukemic cells, and may define cell-permeable proteasome inhibitors as potently anti-leukemic agents which exhibit a moderate hematopoietic toxicity in vitro.